ANALISIS YURIDIS PERLINDUNGAN HUKUM BAGI KORBAN KEKERASAN SEKSUAL PADA ANAK DALAM KASUS PEMERKOSAAN (STUDI PUTUSAN Nomor 4/Pid.Sus/Tahun 2023 PENGADILAN NEGERI SINGARAJA) - Kadek Budi Hartayani; hartono, made sugi; Adnyani, Ni Ketut Sari (Universitas Pendidikan Ganesha, 2025)
Children are the most beautiful gift given by God Almighty who will play an important role in the future of the Indonesian nation. However, currently a big obstacle in the development of the younger generation is the large number of criminal cases of sexual violence. Cases continue to increase and punishment for perpetrators of sexual violence has not had a deterrent effect, making it difficult to hope to reduce the level of sexual violence. Using normative legal research methods as well as Statute approach, Case Approach, and, Conceptual Approach to examine the considerations of judges' decisions in imposing criminal sanctions on perpetrators of sexual violence against children. The aim of this research is to determine the basis for the judge's considerations in providing protection to children as victims of criminal acts of sexual violence in rape cases in case decision Number 4/Pid.Sus/PN Sgr. The type of research used is normative legal research with descriptive research characteristics. Implementation of the judge's authority as regulated in Law no. 48 of 2009 concerning Judicial Power, article 5 paragraph (2), does not yet provide a clear description of the phrase